The effect of replacement of natural sand by manufactured sand on the properties of the concrete - Nadimalla, Altamashuddinkhan; Masjuki, Siti Aliyyah; Khan, Sher Afghan; Pradeep, Aksatha (Institute of Electrical and Electronics Engineers Inc., 2019)
The natural sand which excavated from river bed is used to produced conventional concrete. Depletion of natural sand cause the environmental problem and hence sand excavating is restricted by the government which resulted in shortage and drastically increase in its cost. In order to fulfill the necessity of fine aggregates, an alternative material like M sand can be used in concrete. M sand is obtained by crushing the rocks. In this paper, conventional mix 1:2.32:2.82 (M20) with water to binder ratio is maintained as 0.55 was used in this present study. Here the River Sand is partially and fully replaced with M Sand with different percentages like 0%, 45%, 50%, 55% and 100%. Fresh and hard concrete properties were studied with natural sand substitute by M-Sand. Properties of concrete in fresh state such as workability and in hardened state such as compression test, split tensile test and flexural test were considered in this study.